In vivo validation of psilacetin as a prodrug yielding modestly lower peripheral psilocin exposure than psilocybin - Jones, Nathan T.; Wagner, Laura; Hahn, Molly C. Pellitteri; Scarlett, Cameron O.; Wenthur, Cody J. (Frontiers in Psychiatry, 2024)
Introduction: Use of the psychedelic compound psilocybin in conjunction with psychotherapy has shown promising results in the treatment of psychiatric disorders, though the underlying mechanisms supporting these effects remain unclear. Psilocybin is a schedule I substance that is dephosphorylated in vivo to form an active metabolite, psilocin. Psilacetin, also known as O-Acetylpsilocin or 4-Acetoxy-N, N-dimethyltryptamine (4-AcO-DMT) is an unscheduled compound which has long been suggested as an alternative psilocin prodrug, though direct in vivo support for this hypothesis has thus far been lacking.This study employs liquid chromatography-tandem mass spectrometry (LC-MS/MS) to assess the time-course and plasma concentrations of psilocin following intraperitoneal (IP) administration of psilacetin fumarate or psilocybin to male and female C57Bl6/J mice.Results: Direct comparisons of the time courses for psilocin exposure arising from psilocybin and psilacetin found that psilocybin led to 10-25% higher psilocin concentrations than psilacetin at 15-minutes post-injection. The half-life of psilocin remained around thirty minutes, irrespective of whether it came from psilocybin or psilacetin. Overall, the relative amount of psilocin exposure from psilacetin fumarate was found to be approximately 70% of that from psilocybin.Discussion: These findings provide the first direct support for the long-standing assumption in the field that psilacetin functions as a prodrug for psilocin in vivo. In addition, these results indicate that psilacetin fumarate results in lower peripheral psilocin exposure than psilocybin when dosed on an equimolar basis. Thoughtful substitution of psilocybin with psilacetin fumarate appears to be a viable approach for conducting mechanistic psychedelic research in C57Bl6/J mice.